Laryngopharyngeal reflux disease and risk factor among staff of the tertiary care hospital of Kathmandu, Nepal - Malla, Neeta Shakya; Shrestha, Supri Raj; Shah, Deepa (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Laryngopharyngeal reflux causes significant impairment to quality of life and also predicts serious laryngeal and esophageal pathology. The aim of this study was to diagnose laryngopharyngeal reflux disease (LPRD) using Reflux Symptom Index (RSI) score among the hospital staffs and to know the risk factors associated with it. Material and Methods: The observational descriptive cross-sectional study was done among hospital staffs selected using simple random sampling method working at Manmohan Memorial Hospital, Swoyambhu, Nepal. A self-structured questionnaire prepared was used to collect the demographic data and risk factors associated. Reflux Symptom Index (RSI) a validated selfadministered questionnaires introduced by Belafsky et al. was used to differentiate laryngopharyngeal reflux subject from non-laryngopharyngeal reflux subject. Analysis of data was done and report was prepared. Results: The prevalence of LPRD in the studied population with the use of RSI score was 48.88% (n=78) among 170 participants. The mean RSI score in patient with LPRD was 16.5±2.83 compared to non-LPRD with significant p-value. All the RSI symptoms score has p-value <0.005 between LPRD and non-LPRD which is of significance. Among 62 subjects representing the age group of 30-39 years, half of the percentage had LPRD according to the RSI score. Smoking was found to be related with LPRD. Conclusions: The RSI can easily be included in otolaryngology routines as objective parameters, with low cost and high practicality. Based on the clinical index, the specialist can evaluate the need for further tests.